2017
DOI: 10.1039/c7ta03134c
|View full text |Cite
|
Sign up to set email alerts
|

Functionalised metal–organic frameworks: a novel approach to stabilising single metal atoms

Abstract: We have investigated the potential of metal–organic frameworks for immobilising single atoms of transition metals using a model system of Pd supported on NH2-MIL-101(Cr).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…We have previously showed that functionalisation of UiOs may result in enhanced interaction with embedded Pd NCs, and in the potential change of catalytic performance. 32,33 In particular, the effect of amino groups is worth exploring as i) it can form strong interactions with metal NCs embedded in the MOF's pores potentially mimicking SMSIs [32][33][34] , and furthermore ii) it has been shown to interact strongly with CO 2 and thus their presence may be favourable for its activation and conversion. 35 At the same time, linker functionalisation also may have a long-range effect on the inorganic node (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously showed that functionalisation of UiOs may result in enhanced interaction with embedded Pd NCs, and in the potential change of catalytic performance. 32,33 In particular, the effect of amino groups is worth exploring as i) it can form strong interactions with metal NCs embedded in the MOF's pores potentially mimicking SMSIs [32][33][34] , and furthermore ii) it has been shown to interact strongly with CO 2 and thus their presence may be favourable for its activation and conversion. 35 At the same time, linker functionalisation also may have a long-range effect on the inorganic node (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Since the pristine MIL‐101 was known to have sufficiently high interaction energy with Pd to allow for embedding Pd nanoparticles inside its pores, Szilágyi et al . used the strategy of increasing the MOF−Pd interaction energy to decrease the size of the embedded Pd particle size down to the single‐atom level . This strategy was used in combination with the liquid impregnation method of a suitable Pd precursor (Pd(NO 3 ) 2 or Pd(ac) 2 ) acetonitrile solution, followed by the thorough washing of the sample with acetonitrile to remove any precursor that is not bonded with the functional group, the evaporation of the solvent at elevated temperatures and under dynamic vacuum, and the final reduction of the Pd precursor in an H 2 ‐Ar stream at 200 °C.…”
Section: Synthetic Approachesmentioning
confidence: 99%
“…Szilágyi et al . obtained a metal‐organic framework with Pd immobilised on its pores through a mixture of pore filling and as single atoms . The hydrogen uptake characteristics of the composites material reflected 3 types of hydrogen‐sorbent interactions, including adsorption on the MOF matrix, interstitial hydride formation on the larger ( ca .…”
Section: Embedding Versus Encapsulationmentioning
confidence: 99%
See 2 more Smart Citations